The influence of emotional intelligence competence on teachers' job performance in secondary schools, Sarawak - Lester Anak Surai; Muhamad Suhaimi Taat (Human Resource Management Academic Research Society, 2025)
This study is aimed at identify the influence of emotional intelligence teachers work performance among secondary school teachers in Sarawak, Malaysia. The non-experimental study utilised the survey method by combining several variable sampling techniques to obtain samples. Data was collected through a set of adapted questionnaires administered to 363 teachers. Descriptive analysis shows emotional intelligence competence and teachers work performance being practised at a high level. One-way ANOVA test results show that there is a significant difference in emotional intelligence competence and teachers work performance based on teaching experience. Multiple regression analysis also shows that there is a significant influence of emotional intelligence competence towards teachers work performance. The findings show that the overall contribution predicted by emotional intelligence competence towards teachers work performance is 54.4 percent. Implications and recommendations for further studies are also discussed.